The Potential of Flowering Weeds as Refugia for Predatory Insects at Bantimurung-Bulusaraung National Park, South Sulawesi - Ngatimin, Sri Nur Aminah; Agus, Nurariaty; P. Saranga, Annie (Department of Agronomy and Horticulture, IPB University, 2014)
A study on identication of owering weeds as predatoryinsect alternative foods was conducted at Bantimurung-Bulusaraung National Park, South Sulawesi, Indonesiain February 2013. Among the plants that naturally growin the national park area Cassia siamea andClerodendron paniculatum, which were source of nectarfor insects, particularly butteries. Visits of predatoryinsect to owering weeds and species of both insectsand owering weeds were recorded. The preferredowering weeds visited by the predatory insects are C.striata (Papilionaceae), A.conyzoides (Asteraceae) andL. camara (Verbenaceae) followed by S. nodiflora(Asteraceae), S. rhombifolia (Malvaceae) and L.crustacea (Scrophulariaceae). A large number of adultsand pupae of Coccinella sp. was found in theBantimurung-Bulusaraung National Park.Keywords : nectar, pollen, alternative host, weeds,Indonesia